Evolution of Tandem Repeats Is Mirroring Post-polyploid Cladogenesis in Heliophila (Brassicaceae) - Dogan, Mert; Pouch, Milan; Mandáková, Terezie; Hloušková, Petra; Guo, Xinyi; Winter, Pieter; Chumová, Zuzana; Van Niekerk, Adriaan; Mummenhoff, Klaus; Al-Shehbaz, Ihsan A.; Mucina, Ladislav; Lysak, Martin A. (Frontiers in Plant Science, 2021)
The unigeneric tribe Heliophileae encompassing more than 100 Heliophila species is morphologically the most diverse Brassicaceae lineage. The tribe is endemic to southern Africa, confined chiefly to the southwestern South Africa, home of two biodiversity hotspots (Cape Floristic Region and Succulent Karoo). The monospecific Chamira (C. circaeoides), the only crucifer species with persistent cotyledons, is traditionally retrieved as the closest relative of Heliophileae. Our transcriptome analysis revealed a whole-genome duplication (WGD) ∼26.15–29.20 million years ago, presumably preceding the Chamira/Heliophila split. The WGD was then followed by genome-wide diploidization, species radiations, and cladogenesis in Heliophila. The expanded phylogeny based on nuclear ribosomal DNA internal transcribed spacer (ITS) uncovered four major infrageneric clades (A–D) in Heliophila and corroborated the sister relationship between Chamira and Heliophila. Herein, we analyzed how the diploidization process impacted the evolution of repetitive sequences through low-coverage whole-genome sequencing of 15 Heliophila species, representing the four clades, and Chamira. Despite the firmly established infrageneric cladogenesis and different ecological life histories (four perennials vs. 11 annual species), repeatome analysis showed overall comparable evolution of genome sizes (288–484 Mb) and repeat content (25.04–38.90%) across Heliophila species and clades. Among Heliophila species, long terminal repeat (LTR) retrotransposons were the predominant components of the analyzed genomes (11.51–22.42%), whereas tandem repeats had lower abundances (1.03–12.10%). In Chamira, the tandem repeat content (17.92%, 16 diverse tandem repeats) equals the abundance of LTR retrotransposons (16.69%). Among the 108 tandem repeats identified in Heliophila, only 16 repeats were found to be shared among two or more species; no tandem repeats were shared by Chamira and Heliophila genomes. Six “relic” tandem repeats were shared between any two different Heliophila clades by a common descent. Four and six clade-specific repeats shared among clade A and C species, respectively, support the monophyly of these two clades. Three repeats shared by all clade A species corroborate the recent diversification of this clade revealed by plastome-based molecular dating. Phylogenetic analysis based on repeat sequence similarities separated the Heliophila species to three clades [A, C, and (B+D)], mirroring the post-polyploid cladogenesis in Heliophila inferred from rDNA ITS and plastome sequences.